Development of metabarcoding approaches for investigating temporal and spatial dynamics of meiobenthic communities in estuarine ecosystems - Fais, Maria Pierangela (2021)
Ph.D. Thesis in Biology (Specialty of Sustainable Use of Marine Resources)